Development and evaluation of clozapine intranasal mucoadhesive in situ gels for brain targeting - Ravikrishna, Velupula; Krishnaveni, Janapareddi (Journal of Drug Delivery and Therapeutics, 2019)
Blood brain barrier, poor solubility and low bioavailability (